How to Safely Integrate Multiple Applications on Embedded Many-Core Systems by Applying the "Correctness by Construction" Principle. (12th June 2012) - Hilbrich, Robert
Abstract : Software-intensive embedded systems, especially cyber-physical systems, benefit from the additional performance and the small power envelope offered by many-core processors. Nevertheless, the adoption of a massively parallel processor architecture in the embedded domain is still challenging. The integration of multiple and potentially parallel functions on a chip—instead of just a single function—makes best use of the resources offered. However, this multifunction approach leads to new technical and nontechnical challenges during the integration. This is especially the case for a distributed system architecture, which is subject to specific safety considerations. In this paper, it is argued that these challenges cannot be effectively addressed with traditional engineering approaches. Instead, the application of the "correctness by construction" principle is proposed to improve the integration process.